Mixed integer model for multi-objective short-term cascaded hydropower optimal scheduling - Ge, Xiao-Lin; Zhang, Li-Zi; Wang, Chun-Li (Dianli Xitong Baohu yu Kongzhi, 2013)
The hybrid integer model of multi-objective optimal short-term scheduling for cascaded hydropower system is proposed, so as to fully realize the benefits of hydropower units. Two indicators which are the total surplus load and difference between peak and valley of the total surplus load are introduced to evaluate the scheduling scheme. This model takes into account both the power generation efficiency and performance of peak regulation of hydropower. Since the multi-objectives and the nonlinear constraints are included in the model, fuzzy membership function and mixed-integer modeling method are applied, and the nonlinear multi-objective optimal problem is transferred into the single-objective mixed integer linear programming (MILP) problem. And the proposed model is solved by the advanced MILP software. Through the analysis of real examples of large-scale cascaded hydropower system, the results show that the proposed model is reasonable and effective.